(8t+13)+(-3t+7)=

Simple and best practice solution for (8t+13)+(-3t+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8t+13)+(-3t+7)= equation:


Simplifying
(8t + 13) + (-3t + 7) = 0

Reorder the terms:
(13 + 8t) + (-3t + 7) = 0

Remove parenthesis around (13 + 8t)
13 + 8t + (-3t + 7) = 0

Reorder the terms:
13 + 8t + (7 + -3t) = 0

Remove parenthesis around (7 + -3t)
13 + 8t + 7 + -3t = 0

Reorder the terms:
13 + 7 + 8t + -3t = 0

Combine like terms: 13 + 7 = 20
20 + 8t + -3t = 0

Combine like terms: 8t + -3t = 5t
20 + 5t = 0

Solving
20 + 5t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + 5t = 0 + -20

Combine like terms: 20 + -20 = 0
0 + 5t = 0 + -20
5t = 0 + -20

Combine like terms: 0 + -20 = -20
5t = -20

Divide each side by '5'.
t = -4

Simplifying
t = -4

See similar equations:

| -6+5t= | | 8t-16=40 | | 33-17= | | A=20(3.14)r^2 | | A=20r^2 | | m^2n-mn^2=0 | | 3x+1-4=1 | | (4x+3)(2x^2-9x-5)=0 | | 2n-15n+18=0 | | (x+2)(x+5)(x+8)(x+11)=3640 | | 2n^3-9n^2=0 | | 5x+8x=14 | | -3x^2+4x+1=0 | | 7x-13-6x=10 | | cos(6x)+cos(8x)+cos(18x)+cos(20x)=0 | | -x^2+x+3=0 | | -x+x+3=0 | | 9x+3x-9x=6+8x+11 | | (3w+4)(2w^2+5w-6)= | | 2x+9+2x=-23 | | 0xX=1 | | 3(0)=0 | | 5x+400+9=19 | | x*x-2=0 | | 5x+2=88 | | 120=47.38+0.617x | | y=47.38+0.617x | | r^2-10r+30=0 | | (3x+5)(x-11)=0 | | -5.2m-7.7-1m=-7.9-6.2m-0.2 | | 0.3(0.3(-7)+0.8)=-.3 | | 2x+3=52 |

Equations solver categories